1989
DOI: 10.1148/radiology.170.3.2521735
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction to hepatic venous drainage after liver transplantation: treatment with balloon angioplasty.

Abstract: Stenosis of the suprahepatic inferior vena caval anastomosis is a rare but serious vascular complication after liver transplantation. It may cause significant obstruction to venous drainage from the allograft liver and result in the Budd-Chiari syndrome with massive ascites and pleural effusion causing respiratory compromise. The authors report two such cases in which percutaneous transluminal angioplasty (PTA) of the stenotic anastomosis was performed. This nonsurgical approach resulted in resolution of ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 20 publications
0
32
0
2
Order By: Relevance
“…A l-yr-old girl developed a large right pleural effusion from suprahepatic stenosis of the inferior vena cava 4 mo after liver transplantation (81). She had substantial ascites, which the investigators thought was responsible for development of the effusion.…”
Section: Posttransplant Considerationsmentioning
confidence: 99%
“…A l-yr-old girl developed a large right pleural effusion from suprahepatic stenosis of the inferior vena cava 4 mo after liver transplantation (81). She had substantial ascites, which the investigators thought was responsible for development of the effusion.…”
Section: Posttransplant Considerationsmentioning
confidence: 99%
“…1,2 Balloon angioplasty has been accepted as a safe and effective initial treatment for managing hepatic venous outflow abnormalities following liver transplantation. [3][4][5] However, balloon angioplasty may induce rupture of the fresh anastomosis and also may be ineffective in eliminating various etiologies of venous outflow abnormalities in the early posttransplant period. 6 Stents have usually been used to treat elastic or recurrent stenosis following balloon angioplasty, [7][8][9][10] and there have been a few reports dealing with the long-term (Ͼ1 year) patency of stent-inserted hepatic veins in LDLT.…”
mentioning
confidence: 99%
“…3,4 Decreased liver vascular compliance during acute cellular rejection 5,6 or the use of reduced grafts 7 causing inadequate accommodation of liver blood flow have also been proposed as mechanisms of ascites formation in liver transplant recipients. Recently, Gane et al 8 reported a series of liver transplant recipients who developed massive ascites and coagulation disturbances associated with an underlying hypercoagulable state, but no information on the outcome of these patients was given.…”
mentioning
confidence: 99%